The Influence of Open Access on Institutional Scientific Research Output in MENA Countries: A Comparative Analysis - Marwan Al-Raeei; Chadi Azmeh (SAGE Open)
The release of scientific research has substantial consequences for both the research and the institution in which it was carried out. The selection of publishing methods for scientific articles, such as journal type, quartile, indexed databases, and publishing models, plays a crucial role. Various publishing models exist, including platinum, gold, and green open access. In this study, we examine the implications of open access publishing on reputable journals for Middle East and North Africa (MENA) countries. Additionally, we explore the correlation between open access publishing and MENA country classification according to the World Bank. Bibliometric data from Scopus database are used, focusing on researchers from each MENA country. The World Bank determines if a country is low, middle, or high income. The total number of published documents and open access publications are also considered. The study investigates how open access publishing affects university and research center rankings within MENA countries, utilizing Scopus database information. This encompasses the number of open access documents indexed in Scopus and citations from MENA countries. Multiple ranking systems, such as 2024-QS World University Ranking (QSWUR) and 2023-Scimago Institutions Ranking, are assessed. Findings reveal that open access articles contribute to 72% to 95% of citations received by institutions in MENA countries, highlighting the influence of this publishing model. Additionally, the percentage of open access publishing ranges from 32% in low-income countries to 56% in other MENA countries. The study also demonstrates that MENA countries with higher numbers of open access publications are more likely to have institutions ranked in prestigious systems such as QS World University Ranking and Scimago Institutions. It is discovered that the average percentage of citations received from open access publications indexed in Scopus for MENA countries is 82%, indicating the significant impact of open access publishing on academic citations in these nations. We believe that the procedures done in this study for MENA countries can be generalized further for global countries.